Bored at home?—A systematic review on the effect of environmental enrichment on the welfare of laboratory rats and mice - Mieske, Paul; Hobbiesiefken, Ute; Fischer-Tenhagen, Carola; Heinl, Céline; Hohlbaum, Katharina; Kahnau, Pia; Meier, Jennifer; Wilzopolski, Jenny; Butzke, Daniel; Rudeck, Juliane; Lewejohann, Lars; Diederich, Kai (Frontiers in Veterinary Science, 2022)
Boredom is an emotional state that occurs when an individual has nothing to do, is not interested in the surrounding, and feels dreary and in a monotony. While this condition is usually defined for humans, it may very well describe the lives of many laboratory animals housed in small, barren cages. To make the cages less monotonous, environmental enrichment is often proposed. Although housing in a stimulating environment is still used predominantly as a luxury good and for treatment in preclinical research, enrichment is increasingly recognized to improve animal welfare. To gain insight into how stimulating environments influence the welfare of laboratory rodents, we conducted a systematic review of studies that analyzed the effect of enriched environment on behavioral parameters of animal wellbeing. Remarkably, a considerable number of these parameters can be associated with symptoms of boredom. Our findings show that a stimulating living environment is essential for the development of natural behavior and animal welfare of laboratory rats and mice alike, regardless of age and sex. Conversely, confinement and under-stimulation has potentially detrimental effects on the mental and physical health of laboratory rodents. We show that boredom in experimental animals is measurable and does not have to be accepted as inevitable.